GitLab: how to use a famous collaborative Web application to share your data and program code inside your team (PUBMET, 2023)
The git project is any project (a set of information) managed in a way that preserves the entire history of changes over time, using any implementation of Git program solutions. The workshop will cover basic work procedures in the GitLab WEB interface connected to git project life cycles, from initialization to teamwork on the project. This includes project planning using issues and an issues board. Additionally, it will demonstrate how to connect your local git repository with the GitLab service and how to share it with others. The workshop will briefly address licensing issues, and we will use some creative examples to enhance the learning experience.